Transformation of Islamic Boarding School-Based Character Education: A Study of the Kalpataru Santri Program - Bali, Muhammad Mushfi El Iq; Putriana, Putriana (TA`DIBUNA, 2026)
This study aims to analyze the transformation of pesantren-based character education through the Santri Kalpataru Program at the Nurul Jadid Islamic Boarding School, particularly in the Al-Hasyimiyah area. The background of this study is based on the urgent need to instill values of environmental awareness, social solidarity, and moral consciousness among santri in facing environmental damage and social change. This study uses a qualitative approach with a case study design. Data collection was conducted through in-depth interviews, participatory observation, and documentation collection, which were then analyzed using data reduction, data presentation, and verification techniques to produce conclusions. The results of this study show that the Santri Kalpataru Program is effective in internalizing environmental values through various routine activities such as maintaining the cleanliness of the boarding school, waste management, and reforestation. Collaboration among santri also builds solidarity that strengthens the ecological culture around the pesantren. In addition, santri involvement in community-based activities also increases social awareness and a sense of collective responsibility. This study concludes that pesantren-based character education can be an integrative model for combining religious values, ecological learning, and social character building. These findings have implications for the development of Islamic education theory that is more contextual and relevant to global issues, as well as providing recommendations for the development of an environment-based curriculum in Islamic boarding schools.